Cardiovascular risk in bodybuilders in gyms in São Luís, state of Maranhão - Pestana Brito, Andressa; Sousa Rêgo, Adriana; Nascimento Sousa, Lucian Matheus; Alves da Silva, Francilene; Vieira da Silva Brasil , Gabriella; Barbosa Martins Bragança, Maylla Luanna; Araújo Mendonça Silva, Flor de Maria; Abreu Barbosa, Janaina Maiana (Journal of Health Care, 2021)
the risk of cardiovascular disease, which is the main cause of death in the world. Objective: To verify thefactors associated with anthropometric indicators of cardiovascular risk in bodybuilders in two gyms inSão Luís, state of Maranhão. Material and Methods: This was a cross-sectional study with 302bodybuilders from two gyms in São Luís, state of Maranhão. Data were collected in August andSeptember 2019. A socioeconomic and demographic questionnaire was used. Anthropometricmeasurements were taken. Poisson regression was performed using the StataÂ® 14.0 software. Results:Of the bodybuilding practitioners, 52.3% were female and 86.7% were between 20 and 39 years old. Forthe outcome CC, being female (IRR = 1.10; CI = 1.02-1.18), living with a partner (IRR = 1.17; CI = 1.08-127), having physical activity time from seven to twelve months (IRR = 1.14; CI = 1.01-1.30), beingdiabetic (IRR = 1.06; CI = 1.24-1.69) and having a history of cardiovascular disease in family (IRR =1.07; CI = 0.99-1.16) were a risk factor for CVD. As for the outcome RCEst, being diabetic (IRR = 2.30;CI = 1.34-3.93) was a risk factor for CVD. Regarding the outcome CP, having completed education (IRR= 1.14; CI = 1.02-1.27), smoking (IRR = 1.12; CI = 1.03-1.21), family history of cardiovascular disease(IRR = 1.07; CI = 1.00-1.15) were a risk factor for CVD. As for the WHR indicator, being diabetic (IRR= 9.47; CI = 1.21-2.00) was a risk factor for CVD. Conclusion: There were several risk factors associatedwith anthropometric indicators of cardiovascular risk (WC, WHtR, CP and WHR) in bodybuildingpractitioners.
Keywords: risk factors; anthropometric indicators; cardiovascular diseases; weight training